The Compotition And Function of Heo Musical Instrument at Feotnai Insana Studio Regency of North Central Timor, East Nusa Tenggara Province - Amasanan, Yohanes Devriezen; Sumaryanto, Totok; syakir, Syakir (Catharsis, 2019)
Heo is a traditional musical instrument typical of the people of Timor, especially the Dawan Tribe, Insana District, East Nusa Tenggara, which is used as an accompaniment to dances, songs, and poems.One of the studio that still maintains this instrument specifically in its composition and function is the Feotnai Insana Studio. This study examines and analyzes the composition of the Heo musical instrument in Sanggar Feotnai Insana and its functions in society. The method used in this research is qualitative method. The technique of collecting data using observation, interview, document study techniques. The data validity technique uses triangulation methods / techniques. Data analysis techniques use the theory of music composition and the function of music in society. The results of this study obtained facts in the composition of the heo musical instrument playing: Allegretto Tempo: 106 bpm, the time signature using a 2/4 beat,the rhythmplayed using a Tamburwith a Timorese rhyme, the melody played by the Heo and Fekoo and harmony played by the Leko Boko by using the C chord. The benefits of this study can expand the reader's perspective on the traditional music of the Dawan Tribe, Heo and provide information about the composition of the Heo musical instrument in the community which also supports Heo's existence.